2013
DOI: 10.1007/s10995-013-1370-2
|View full text |Cite
|
Sign up to set email alerts
|

Preconception Healthcare and Congenital Disorders: Systematic Review of the Effectiveness of Preconception Care Programs in the Prevention of Congenital Disorders

Abstract: Congenital disorders are a leading cause of global burden of disease; the birth prevalence remains constant at 6%. Initiating preconception care before pregnancy may be an effective strategy to reduce congenital disorders and improve the health of reproductive-age women. Our objectives are: (1) To identify components of preconception interventions, (2) to assess the effectiveness of preconception interventions in reducing the burden of congenital disorders, and (3) to prioritize these interventions. Medline an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
36
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 44 publications
0
36
0
1
Order By: Relevance
“…Further recommendations include pre-conception folic acid supplementation in order to prevent congenital malformations in newborns and possibly improve neurodevelopmental outcomes (Harden et al, 2009b;Shannon et al, 2014). Safety data on the newer AEDs are quite sparse.…”
Section: Women With Epilepsy: Clinically Relevant Issuesmentioning
confidence: 99%
“…Further recommendations include pre-conception folic acid supplementation in order to prevent congenital malformations in newborns and possibly improve neurodevelopmental outcomes (Harden et al, 2009b;Shannon et al, 2014). Safety data on the newer AEDs are quite sparse.…”
Section: Women With Epilepsy: Clinically Relevant Issuesmentioning
confidence: 99%
“…They concluded that the risk of major congenital malformations in the offspring of women with epilepsy is possibly decreased by folic acid supplementation (two adequately sensitive Class III studies) and they recommended that preconceptional folic acid supplementation in women with epilepsy may be considered to reduce the risk of major congenital malformations (Level C) [3]. They also stated that ''there was insufficient published information to address the dosing of folic acid and whether higher doses offer greater protective benefit to women with epilepsy taking AEDs'' [3]. However, women with epilepsy are often recognized as a high risk group and guidelines consistently recommend prescription of high doses (up to 5 mg/-day) of folic acid supplementation in this population [4,5].…”
Section: Folic Acid Supplementation In Women With Epilepsymentioning
confidence: 99%
“…The current folic acid supplementation recommendation is that all women of childbearing potential be supplemented with at least 0.4 mg of folic acid daily prior to conception and during pregnancy [2]. Most experts agree that folic acid supplementation is a key preconception intervention, particularly in women with epilepsy who take antiepileptic drugs (AEDs) [3]. In this review, I will try to emphasize that there is insufficient information to address the optimal dosing of folic acid supplementation in women with epilepsy, who take AEDs.…”
Section: Introductionmentioning
confidence: 99%
“…BDs are an important public health problem due to their overall incidence, with major congenital anomalies occurring in approximately 2-3% of live births in the European Union (EU) (Taruscio et al, 2011). The 2006 March of Dimes report estimated that, on average, 7.9 million children (approximately 6% of total births worldwide) are born with BDs (Shannon et al, 2014). However, the incidence is 5.6% in China, and there are 0.9 million new cases every year according to The Prevention Report of China's Birth Defects (2012), which was published by China's Ministry of Health.…”
Section: Introductionmentioning
confidence: 99%